2021
DOI: 10.1007/s11067-021-09547-4
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Attribute Community Detection in International Trade Network

Abstract: Understanding the structure of communities in a network has a great importance in the economic analysis. Communities are indeed characterized by specific properties, that are different from those of both the individual nodes and the whole network, and they can affect various processes on the network. In the International Trade Network, community detection aims to search sets of countries (or of trade sectors) which have a high intra-cluster connectivity and a low inter-cluster connectivity. In general, exchang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Furthermore, we notice that relevant sectors, based on multilayers hubs and scores and reported in Table 1, play a crucial role for these countries (see, for instance, node EGW in the three networks). Based on broadcasting and receiving rankings, it could be observed that the topranked countries are representative of three largest clusters detected by community detection methods on the international trade network (see, for example, [2], [6], [13], [16], [18], [20], [39] and [42]): the American cluster, the Pacific cluster and the European cluster. In addition to the information mined by the mesoscale structure, the proposed approach highlights the pivotal countries of each community.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we notice that relevant sectors, based on multilayers hubs and scores and reported in Table 1, play a crucial role for these countries (see, for instance, node EGW in the three networks). Based on broadcasting and receiving rankings, it could be observed that the topranked countries are representative of three largest clusters detected by community detection methods on the international trade network (see, for example, [2], [6], [13], [16], [18], [20], [39] and [42]): the American cluster, the Pacific cluster and the European cluster. In addition to the information mined by the mesoscale structure, the proposed approach highlights the pivotal countries of each community.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies based on complex network theory have focused mainly on the structural characteristics and evolution patterns of the trade network from many aspects, such as detecting trade communities formed by some countries with tight trade relationships [26] , [27] , [28] , analyzing the structure of the core and periphery [29] , evaluating the centrality of countries [25] , [30] , identifying the relationships between the centrality of countries and other country characteristics [30] , [31] , estimating or predicting trade flows in the trade network [32] , [33] , [34] , revealing the impact factors of trade network formation [27] , [29] , investigating changes in structural characteristics during the evolution [35] , [36] , exploring risk transmission in the trade network [37] , [38] , and identifying the robustness of the trade network [39] , [40] .…”
Section: Literature Reviewmentioning
confidence: 99%